INSTITUTIONAL ECONOMICS AND HUMAN CAPITAL AS DRIVERS OF LABOR MARKET TRANSFORMATION: A STRUCTURAL PERSPECTIVE FROM INDONESIA - Erwin Erwin; Dirmansyah Darwin; Adi Zulkarnaen; Muh Fardan Ngoyo; Hafid Sumarwadji (Program Studi Perbankan Syariah, IAIN Palopo, 2026)
Labor market transformation from traditional to modern sectors is a critical milestone for economic development, yet regional disparities in emerging economies persist. This study investigates the impact of human capital and institutional quality on labor market transformation across 34 provinces in Indonesia over the period of 2015–2025. Employing a panel data regression with a Fixed Effect Model (FEM) approach on 374 observations, and controlling for economic growth and regional investment, the empirical results reveal that both human capital and institutional quality significantly drive the structural shift of labor toward the industrial and service sectors. Specifically, higher educational attainment and better democratic governance accelerate the absorption of labor into high-productivity sectors. Furthermore, economic growth and investment act as robust catalysts in this structural transformation. These findings suggest that to optimize the demographic dividend, regional policymakers must not rely solely on physical investment but should synergize aggressive human capital development with institutional governance reforms